Germacyclobutenes : structure, strain energy and ring-opening reaction. - Tan, Samuel Qi'en. (2010)
The structure, ring strain energy and ring-opening reaction of 9 germacyclobutenes, including monogermacyclobutenes, digermacyclobutenes, trigermacyclobutenes and tetragermcyclobutene are systematically studied at the B3LYP/6-311+G(d,p) level. The minima of various ring structures are determined by optimization and further verified with frequency analysis. From this, the structural geometries and symmetries of the structures can be studied. Moving on, the strain energies for the 9 molecules are calculated using isodesmic equation. The ring-opening reaction mechanism of the 9 germacyclobutene structures is examined by finding the intermediate states and products of the ringed-structures through optimization. The energies of the intermediate states and products are compared to the ground states to find activation energy and heat of reaction respectively. Graphs are then plotted for comparison among the 9 structures and down the homologous series. On the whole, results show that strain energy, activation energy and heat of reaction vary significantly across the 9 structures. There is however, a trend when comparing structures down the group 14 homologous series. This shall be further evaluated in this paper.